Survival outcomes of consolidation chemoradiotherapy in esophageal cancer patients who achieve clinical complete response but refuse surgery after neoadjuvant chemoradiotherapy - Fang, Hsin-Yueh; Chao, Yin-Kai; Chang, Hsien-Kun; Tseng, Chen-Kan; Liu, Yun-Hen (Diseases of the esophagus, 2017)
SUMMARY Some esophageal cancer patients may be reluctant to accept the scheduled resection after neoadjuvant chemoradiotherapy (nCRT) because of its potential negative impact on quality of life as a result of high morbidity. This study was performed to investigate the survival outcomes of these patients. Between 2000 and 2012, we identified 190 patients with resectable esophageal squamous cell carcinoma (ESCC) who did not proceed to surgery following nCRT. Subjects who had a clinical complete response (cCR) and were medically fit for surgery were deemed eligible. Survival rates, recurrence patterns, and risk factors for recurrence served as the main outcome measures. The study cohort consisted of 73 patients (67 males and 6 females; mean age: 61.3 years). The 5-year overall survival was 39.6% (median survival time: 46.77 months). Cancer recurrences were observed in 44 patients (60.2%), with locoregional recurrence (LR) being the most common failure pattern (n = 35). Endoscopic findings after nCRT were the most important independent predictor of LR identified in multivariate analysis. Compared with the ‘normal findings’ subgroup, the odds ratios for LR in cCR patients who refused surgery were 4.774 (P = 0.026) and 2.844 (P = 0.16) in the ‘scar’ and ‘other findings’ subgroups, respectively. Patients with ‘normal findings’ had the lowest rate of LR (22.2%), with no recurrences occurring within the first 6 months. Sixty percent of ESCC patients who achieve cCR following nCRT but refuse esophagectomy develop disease recurrence, with LR being the most common pattern. Post-nCRT endoscopic findings may serve as a predictor for LR.